Experimental and numerical study of compression after impact of sandwich structures with metallic skins - Aminanda, Yulfian; Castanie, Bruno; Barrau, Jean-Jacques; Thevenet, Pascal (Elsevier, 2009)
A finite element model is proposed to determine the residual print of sandwich structures with Nomex honeycomb core and metallic skins indented by a spherical indenter and to simulate its behavior when this indented structure is subjected to lateral compressive loading (known as CAI/ Compression after impact). The particularities of this model rely on representing the honeycomb with a grid of nonlinear springs which its behavior law calibrated from uniform compression test. This simple model, after integrating the cycle behavior law of honeycomb, allows predicting the geometry of residual print with a good precision. This model is then developed to propose a complete computation from indentation, residual print geometry to lateral compressive loading after indentation (CAI). This model also allows predicting numerically the residual strength of structure in CAI and the elliptical evolution of residual print geometry during CAI loading. A good correlation with test results is obtained except for the very small residual print depth.